Call Center Training-Teams & Quality - Giere, Nancy (Association for Talent Development, 2000)
Learn how to develop performance measurement criteria for call center agents plus how to hire for attitude and train for skill by finding service-minded individuals who are able to learn an organization's products, services, and systems.